NPAS2 regulates proliferation of acute myeloid leukemia cells via CDC25A‐mediated cell cycle progression and apoptosis. Issue 5 (9th December 2018) - Song, Bin; Chen, Yan; Liu, Yuhong; Wan, Chucheng; Zhang, Longjin; Zhang, Wanggang
Abstract: Promoted proliferation and associated suppression of apoptosis at various stages of myeloid differentiation are well‐known features of acute myeloid leukemia (AML), but understanding of the molecular processes involved remains limited. As a crucial circadian agent, neuronal PAS domain protein 2 ( NPAS2 ) is widely recognized as a promising predictor of clinical outcome in various malignancies. Nevertheless, the understanding of its influence on AML is insufficient. Using KD cells and expression assays, we carried out detailed investigation of the role of NPAS2 in AML in vivo and in vitro. Firstly, we found that NPAS2 expression was elevated in AML cells both in vivo and in vitro. NPAS2 knockdown via lentiviral infection clearly suppressed proliferation of MV4‐11 and MOLM‐14 cells. Additionally, NPAS2 knockdown caused G1/S cell cycle arrest (CCA), which inhibited CDC25A expression. Moreover, NPAS2 knockdown promoted cell death, as evidenced by increased caspase‐3 cleavage, and change in Bcl2/Bax production. Excessive CDC25A expression eliminated G1/S CCA triggered by NPAS2 knockdown and death of NPAS2 knocked down MOLM and MV4‐11 cells. The expression of CDC25A was stabilized by NPAS2, which induced cell cycle progression and participated in suppression of cell death by modulating caspase‐3 cleavage, and expression of Bcl2/Bax. We therefore indicated NPAS2 to be a crucial modulator of survival as well as proliferation. Our research sheds light on the etiology of the proliferation of promyelocytes modulated via NPAS2 with regard to AML. Abstract : In summary, our research throws light upon the etiology of the influence of NPAS2 on proliferation in acute myeloid leukemia (AML) cell lines. We have shown that NPAS2 can influence expression of CDC25A, which, in turn, can regulate cell‐cycle distribution as well as death in AML cells. We therefore suggest that NPAS2 expression has potential as a marker of clinical outcome in AML